Application of Mozart Classical Music Therapy to Reduce Auditory Hallucinations in Mentally Ill Patients in the Larasati Room of Dr. Arif Zainuddin Surakarta - Reyhanna Rizqi Utami; Arif Widodo (PSPP JOURNALS, 2026)
Auditory hallucinations are one of the most common positive symptoms experienced by patients with mental disorders and can disrupt psychological and social functioning, as well as their quality of life. Treatment of auditory hallucinations is generally through pharmacological therapy, but non-pharmacological interventions are needed as complementary therapies to improve the holistic success of treatment. One such non-pharmacological intervention is Mozart's classical music therapy. This study aims to determine the effectiveness of Mozart's classical music therapy in reducing auditory hallucinations in patients with mental disorders in the Larasati Ward of Dr. Arif Zainuddin Hospital, Surakarta. This study used a case study design with a nursing care approach. The subjects were two patients with mental disorders experiencing auditory hallucinations, selected purposively according to inclusion and exclusion criteria. The Mozart classical music therapy intervention was administered for approximately 15–20 minutes, three times a week for one month. Data were collected through a nursing assessment using interviews and observations, which included subjective and objective data before and after the intervention. Data analysis was conducted descriptively by comparing the patients' conditions before and after the intervention. The study showed a reduction in auditory hallucination symptoms after Mozart classical music therapy. Subjectively, patients reported a reduction in the number of voices or whispers they heard. Objectively, patients appeared calmer, more relaxed, more cooperative, decreased the frequency of self-talk, and were able to focus during therapy. The conclusion of this study is that Mozart classical music therapy is effective as a non-pharmacological nursing intervention in reducing auditory hallucinations in patients with mental disorders and can be recommended as a supportive therapy in psychiatric nursing care.